1988
DOI: 10.1152/jappl.1988.64.3.1257
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of ventilation in elderly subjects awake and asleep

Abstract: We studied the periodicities of ventilation in elderly subjects using digital comb filtering. Two groups of subjects were studied, those with and without sleep apnea. Measurements were made in wakefulness, stage 1-2 sleep, and where possible in stage 3-4 sleep. For each of the digital filters we calculated the average power of the oscillatory output. To compare subject groups we first specifically determined the average power in the filter with the maximum output. The mean of this measurement was greater in el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 0 publications
4
31
0
1
Order By: Relevance
“…Arousal from sleep leads to hyperventilation and the resulting hypocapnia (and reduced central respiratory drive) could promote a CSA following sleep resumption. The correlation between fluctuations in EEG frequency and changes in tidal volume in elderly people support this idea [44]. In the present study, sleep onset did not produce significant periodic or unstable breathing in elderly or young people.…”
Section: Mechanisms Of Csa In the Elderlysupporting
confidence: 82%
“…Arousal from sleep leads to hyperventilation and the resulting hypocapnia (and reduced central respiratory drive) could promote a CSA following sleep resumption. The correlation between fluctuations in EEG frequency and changes in tidal volume in elderly people support this idea [44]. In the present study, sleep onset did not produce significant periodic or unstable breathing in elderly or young people.…”
Section: Mechanisms Of Csa In the Elderlysupporting
confidence: 82%
“…21 In an elderly population, periodical breathing with subsequent hypoxemia is more common. 22 It has been suggested that an underlying defect of chemoreceptor sensitivity can lead to an unstable feedback control of respiration 23 and contribute to abnormal blood pressure regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology of the disease probably changes due to changes in parapharyngeal fat pad deposition [30], serotonergic dysregulation of brainstem respiratory control (due to ''wear and tear'') [31] and age-related changes in bony structures, such as edentulism [32]. Variations in neuromuscular control of the upper airway become more important in the elderly [33], and increased background prevalences of cardiac and cerebrovascular disease increase the likelihood of periodic breathing. The clinical phenotype of OSAHS also changes.…”
Section: The Phenotypic Complexity Of Osahs Heterogeneity Of Osahsmentioning
confidence: 99%